Combined Measurement of the Higgs Boson Mass in pp Collisions at root s=7 and 8 TeV with the ATLAS and CMS Experiments - Abbott, B.; Abdallah, J.; Abdinov, O.; Aben, R.; Abolins, M.; AbouZeid, O. S.; Abramowicz, H.; Abreu, H.; Abreu, R.; Abulaiti, Y.; Acharya, B. S.; Adamczyk, L.; et al. (My University, 2015)
A measurement of the Higgs boson mass is presented based on the combined data samples of the ATLAS and CMS experiments at the CERN LHC in the H --> gamma gamma and H --> ZZ --> 4l decay channels. The results are obtained from a simultaneous fit to the reconstructed invariant mass peaks in the two channels and for the two experiments. The measured masses from the individual channels and the two experiments are found to be consistent among themselves. The combined measured mass of the Higgs boson is m(H) = 125.09 +/- 0.21 (stat) +/- 0.11 (syst) GeV.
Citation: Aad, G., Abbott, B., Abdallah, J., Abdinov, O., Aben, R., Abolins, M., . . . Collaboration, C. M. S. (2015). Combined Measurement of the Higgs Boson Mass in pp Collisions at root s=7 and 8 TeV with the ATLAS and CMS Experiments. Physical Review Letters, 114(19), 33. doi:10.1103/PhysRevLett.114.191803
Additional Authors: Adomeit, S.;Adye, T.;Affolder, A. A.;Agatonovic-Jovin, T.;Aguilar-Saavedra, J. A.;Ahlen, S. P.;Ahmadov, F.;Aielli, G.;Akerstedt, H.;Akesson, T. P. A.;Akimoto, G.;Akimov, A. V.;Alberghi, G. L.;Albert, J.;Albrand, S.;Verzini, M. J. A.;Aleksa, M.;Aleksandrov, I. N.;Alexa, C.;Alexander, G.;Alexopoulos, T.;Alhroob, M.;Alimonti, G.;Alio, L.;Alison, J.;Alkire, S. P.;Allbrooke, B. M. M.;Allport, P. P.;Aloisio, A.;Alonso, A.;Alonso, F.;Alpigiani, C.;Altheimer, A.;Gonzalez, B. A.;Piqueras, D. A.;Alviggi, M. G.;Amadio, B. T.;Amako, K.;Coutinho, Y. A.;Amelung, C.;Amidei, D.;Dos Santos, S. P. A.;Amorim, A.;Amoroso, S.;Amram, N.;Amundsen, G.;Anastopoulos, C.;Ancu, L. S.;Andari, N.;Andeen, T.;Anders, C. F.;Anders, G.;Anders, J. K.;Anderson, K. J.;Andreazza, A.;Andrei, V.;Angelidakis, S.;Angelozzi, I.;Anger, P.;Angerami, A.;Anghinolfi, F.;Anisenkov, A. V.;Anjos, N.;Annovi, A.;Antonelli, M.;Antonov, A.;Antos, J.;Anulli, F.;Aoki, M.;Bella, L. A.;Arabidze, G.;Arai, Y.;Araque, J. P.;Arce, A. T. H.;Arduh, F. A.;Arguin, J. F.;Argyropoulos, S.;Arik, M.;Armbruster, A. J.;Arnaez, O.;Arnal, V.;Arnold, H.;Arratia, M.;Arslan, O.;Artamonov, A.;Artoni, G.;Asai, S.;Asbah, N.;Ashkenazi, A.;Asman, B.;Asquith, L.;Assamagan, K.;Astalos, R.;Atkinson, M.;Atlay, N. B.;Auerbach, B.;Augsten, K.;Aurousseau, M.;Avolio, G.;Axen, B.;Ayoub, M. K.;Azuelos, G.;Baak, M. A.;Baas, A. E.;Bacci, C.;Bachacou, H.;Bachas, K.;Backes, M.;Backhaus, M.;Badescu, E.;Bagiacchi, P.;Bagnaia, P.;Bai, Y.;Bain, T.;Baines, J. T.;Baker, O. K.;Balek, P.;Balestri, T.;Balli, F.;Banas, E.;Banerjee, S.;Bannoura, A. A. E.;Bansil, H. S.;Barak, L.;Baranov, S. P.;Barberio, E. L.;Barberis, D.;Barbero, M.;Barillari, T.;Barisonzi, M.;Barklow, T.;Barlow, N.;Barnes, S. L.;Barnett, B. M.;Barnett, R. M.;Barnovska, Z.;Baroncelli, A.;Barone, G.;Barr, A. J.;Barreiro, F.;da Costa, J. B. G.;Bartoldus, R.;Barton, A. E.;Bartos, P.;Bassalat, A.;Basye, A.;Bates, R. L.;Batista, S. J.;Batley, J. R.;Battaglia, M.;Bauce, M.;Bauer, F.;Bawa, H. S.;Beacham, J. B.;Beattie, M. D.;Beau, T.;Beauchemin, P. H.;Beccherle, R.;Bechtle, P.;Beck, H. P.;Becker, K.;Becker, M.;Becker, S.;Beckingham, M.;Becot, C.;Beddall, A. J.;Beddall, A.;Bednyakov, V. A.;Bee, C. P.;Beemster, L. J.;Beermann, T. A.;Begel, M.;Behr, J. K.;Belanger-Champagne, C.;Bell, W. H.;Bella, G.;Bellagamba, L.;Bellerive, A.;Bellomo, M.;Belotskiy, K.;Beltramello, O.;Benary, O.;Benchekroun, D.;Bender, M.;Bendtz, K.;Benekos, N.;Benhammou, Y.;Noccioli, E. B.;Garcia, J. A. B.;Benjamin, D. P.;Bensinger, J. R.;Bentvelsen, S.;Beresford, L.;Beretta, M.;Berge, D.;Kuutmann, E. B.;Berger, N.;Berghaus, F.;Beringer, J.;Bernard, C.;Bernard, N. R.;Bernius, C.;Bernlochner, F. U.;Berry, T.;Berta, P.;Bertella, C.;Bertoli, G.;Bertolucci, F.;Bertsche, C.;Bertsche, D.;Besana, M. I.;Besjes, G. J.;Bylund, O. B.;Bessner, M.;Besson, N.;Betancourt, C.;Bethke, S.;Bevan, A. J.;Bhimji, W.;Bianchi, R. M.;Bianchini, L.;Bianco, M.;Biebel, O.;Bieniek, S. P.;Biglietti, M.;De Mendizabal, J. B.;Bilokon, H.;Bindi, M.;Binet, S.;Bingul, A.;Bini, C.;Black, C. W.;Black, J. E.;Black, K. M.;Blackburn, D.;Blair, R. E.;Blanchard, J. B.;Blanco, J. E.;Blazek, T.;Bloch, I.;Blocker, C.;Blum, W.;Blumenschein, U.;Bobbink, G. J.;Bobrovnikov, V. S.;Bocchetta, S. S.;Bocci, A.;Bock, C.;Boehler, M.;Bogaerts, J. A.;Bogdanchikov, A. G.;Bohm, C.;Boisvert, V.;Bold, T.;Boldea, V.;Boldyrev, A. S.;Bomben, M.;Bona, M.;Boonekamp, M.;Borisov, A.;Borissov, G.;Borroni, S.;Bortfeldt, J.;Bortolotto, V.;Bos, K.;Boscherini, D.;Bosman, M.;Boudreau, J.;Bouffard, J.;Bouhova-Thacker, E. V.;Boumediene, D.;Bourdarios, C.;Bousson, N.;Boveia, A.;Boyd, J.;Boyko, I. R.;Bozic, I.;Bracinik, J.;Brandt, A.;Brandt, G.;Brandt, O.;Bratzler, U.;Brau, B.;Brau, J. E.;Braun, H. M.;Brazzale, S. F.;Brendlinger, K.;Brennan, A. J.;Brenner, L.;Brenner, R.;Bressler, S.;Bristow, K.;Bristow, T. M.;Britton, D.;Britzger, D.;Brochu, F. M.;Brock, I.;Brock, R.;Bronner, J.;Brooijmans, G.;Brooks, T.;Brooks, W. K.;Brosamer, J.;Brost, E.;Brown, J.;de Renstrom, P. A. B.;Bruncko, D.;Bruneliere, R.;Bruni, A.;Bruni, G.;Bruschi, M.;Bryngemark, L.;Buanes, T.;Buat, Q.;Buchholz, P.;Buckley, A. G.;Buda, S. I.;Budagov, I. A.;Buehrer, F.;Bugge, L.;Bugge, M. K.;Bulekov, O.;Bullock, D.;Burckhart, H.;Burdin, S.;Burghgrave, B.;Burke, S.;Burmeister, I.;Busato, E.;Buscher, D.;Buscher, V.;Bussey, P.;Buszello, C. P.;Butler, J. M.;Butt, A. I.;Buttar, C. M.;Butterworth, J. M.;Butti, P.;Buttinger, W.;Buzatu, A.;Buzykaev, R.;Urban, S. C.;Caforio, D.;Cairo, V. M.;Cakir, O.;Calafiura, P.;Calandri, A.;Calderini, G.;Calfayan, P.;Caloba, L. P.;Calvet, D.;Calvet, S.;Toro, R. C.;Camarda, S.;Camarri, P.;Cameron, D.;Caminada, L. M.;Armadans, R. C.;Campana, S.;Campanelli, M.;Campoverde, A.;Canale, V.;Canepa, A.;Bret, M. C.;Cantero, J.;Cantrill, R.;Cao, T.;Garrido, Mdmc;Caprini, I.;Caprini, M.;Capua, M.;Caputo, R.;Cardarelli, R.;Carli, T.;Carlino, G.;Carminati, L.;Caron, S.;Carquin, E.;Carrillo-Montoya, G. D.;Carter, J. R.;Carvalho, J.;Casadei, D.;Casado, M. P.;Casolino, M.;Castaneda-Miranda, E.;Castelli, A.;Gimenez, V. C.;Castro, N. F.;Catastini, P.;Catinaccio, A.;Catmore, J. R.;Cattai, A.;Caudron, J.;Cavaliere, V.;Cavalli, D.;Cavalli-Sforza, M.;Cavasinni, V.;Ceradini, F.;Cerio, B. C.;Cerny, K.;Cerqueira, A. S.;Cerri, A.;Cerrito, L.;Cerutti, F.;Cerv, M.;Cervelli, A.;Cetin, S. A.;Chafaq, A.;Chakraborty, D.;Chalupkova, I.;Chang, P.;Chapleau, B.;Chapman, J. D.;Charlton, D. G.;Chau, C. C.;Barajas, C. A. C.;Cheatham, S.;Chegwidden, A.;Chekanov, S.;Chekulaev, S. V.;Chelkov, G. A.;Chelstowska, M. A.;Chen, C.;Chen, H.;Chen, K.;Chen, L.;Chen, S.;Chen, X.;Chen, Y.;Cheng, H. C.;Cheng, Y.;Cheplakov, A.;Cheremushkina, E.;El Moursli, R. C.;Chernyatin, V.;Cheu, E.;Chevalier, L.;Chiarella, V.;Childers, J. T.;Chiodini, G.;Chisholm, A. S.;Chislett, R. T.;Chitan, A.;Chizhov, M. V.;Choi, K.;Chouridou, S.;Chow, B. K. B.;Christodoulou, V.;Chromek-Burckhart, D.;Chu, M. L.;Chudoba, J.;Chuinard, A. J.;Chwastowski, J. J.;Chytka, L.;Ciapetti, G.;Ciftci, A. K.;Cinca, D.;Cindro, V.;Cioara, I. A.;Ciocio, A.;Citron, Z. H.;Ciubancan, M.;Clark, A.;Clark, B. L.;Clark, P. J.;Clarke, R. N.;Cleland, W.;Clement, C.;Coadou, Y.;Cobal, M.;Coccaro, A.;Cochran, J.;Coffey, L.;Cogan, J. G.;Cole, B.;Cole, S.;Colijn, A. P.;Collot, J.;Colombo, T.;Compostella, G.;Muino, P. C.;Coniavitis, E.;Connell, S. H.;Connelly, I. A.;Consonni, S. M.;Consorti, V.;Constantinescu, S.;Conta, C.;Conti, G.;Conventi, F.;Cooke, M.;Cooper, B. D.;Cooper-Sarkar, A. M.;Cornelissen, T.;Corradi, M.;Corriveau, F.;Corso-Radu, A.;Cortes-Gonzalez, A.;Cortiana, G.;Costa, G.;Costa, M. J.;Costanzo, D.;Cote, D.;Cottin, G.;Cowan, G.;Cox, B. E.;Cranmer, K.;Cree, G.;Crepe-Renaudin, S.;Crescioli, F.;Cribbs, W. A.;Ortuzar, M. C.;Cristinziani, M.;Croft, V.;Crosetti, G.;Donszelmann, T. C.;Cummings, J.;Curatolo, M.;Cuthbert, C.;Czirr, H.;Czodrowski, P.;D'Auria, S.;D'Onofrio, M.;De Sousa, Mjds;Da Via, C.;Dabrowski, W.;Dafinca, A.;Dai, T.;Dale, O.;Dallaire, F.;Dallapiccola, C.;Dam, M.;Dandoy, J. R.;Dang, N. P.;Daniells, A. C.;Danninger, M.;Hoffmann, M. D.;Dao, V.;Darbo, G.;Darmora, S.;Dassoulas, J.;Dattagupta, A.;Davey, W.;David, C.;Davidek, T.;Davies, E.;Davies, M.;Davison, P.;Davygora, Y.;Dawe, E.;Dawson, I.;Daya-Ishmukhametova, R. K.;De, K.;de Asmundis, R.;De Castro, S.;De Cecco, S.;De Groot, N.;de Jong, P.;De la Torre, H.;De Lorenzi, F.;De Nooij, L.;De Pedis, D.;De Salvo, A.;De Sanctis, U.;De Santo, A.;De Regie, J. B. D.;Dearnaley, W. J.;Debbe, R.;Debenedetti, C.;Dedovich, D. V.;Deigaard, I.;Del Peso, J.;Del Prete, T.;Delgove, D.;Deliot, F.;Delitzsch, C. M.;Deliyergiyev, M.;Dell'Acqua, A.;Dell'Asta, L.;Dell'Orso, M.;Della Pietra, M.;della Volpe, D.;Delmastro, M.;Delsart, P. A.;Deluca, C.;DeMarco, D. A.;Demers, S.;Demichev, M.;Demilly, A.;Denisov, S. P.;Derendarz, D.;Derkaoui, J. E.;Derue, F.;Dervan, P.;Desch, K.;Deterre, C.;Deviveiros, P. O.;Dewhurst, A.;Dhaliwal, S.;Di Ciaccio, A.;Di Ciaccio, L.;Di Domenico, A.;Di Donato, C.;Di Girolamo, A.;Di Girolamo, B.;Di Mattia, A.;Di Micco, B.;Di Nardo, R.;Di Simone, A.;Di Sipio, R.;Di Valentino, D.;Diaconu, C.;Diamond, M.;Dias, F. A.;Diaz, M. A.;Diehl, E. B.;Dietrich, J.;Diglio, S.;Dimitrievska, A.;Dingfelder, J.;Dita, P.;Dita, S.;Dittus, F.;Djama, F.;Djobava, T.;Djuvsland, J. I.;do Vale, M. A. B.;Dobos, D.;Dobre, M.;Doglioni, C.;Dohmae, T.;Dolejsi, J.;Dolezal, Z.;Dolgoshein, B. A.;Donadelli, M.;Donati, S.;Dondero, P.;Donini, J.;Dopke, J.;Doria, A.;Dova, M. T.;Doyle, A. T.;Drechsler, E.;Dris, M.;Dubreuil, E.;Duchovni, E.;Duckeck, G.;Ducu, O. A.;Duda, D.;Dudarev, A.;Duflot, L.;Duguid, L.;Duhrssen, M.;Dunford, M.;Yildiz, H. D.;Duren, M.;Durglishvili, A.;Duschinger, D.;Dyndal, M.;Eckardt, C.;Ecker, K. M.;Edgar, R. C.;Edson, W.;Edwards, N. C.;Ehrenfeld, W.;Eifert, T.;Eigen, G.;Einsweiler, K.;Ekelof, T.;El Kacimi, M.;Ellert, M.;Elles, S.;Ellinghaus, F.;Elliot, A. A.;Ellis, N.;Elmsheuser, J.;Elsing, M.;Emeliyanov, D.;Enari, Y.;Endner, O. C.;Endo, M.;Engelmann, R.;Erdmann, J.;Ereditato, A.;Ernis, G.;Ernst, J.;Ernst, M.;Errede, S.;Ertel, E.;Escalier, M.;Esch, H.;Escobar, C.;Esposito, B.;Etienvre, A. I.;Etzion, E.;Evans, H.;Ezhilov, A.;Fabbri, L.;Facini, G.;Fakhrutdinov, R. M.;Falciano, S.;Falla, R. J.;Faltova, J.;Fang, Y.;Fanti, M.;Farbin, A.;Farilla, A.;Farooque, T.;Farrell, S.;Farrington, S. M.;Farthouat, P.;Fassi, F.;Fassnacht, P.;Fassouliotis, D.;Giannelli, M. F.;Favareto, A.;Fayard, L.;Federic, P.;Fedin, O. L.;Fedorko, W.;Feigl, S.;Feligioni, L.;Feng, C.;Feng, E. J.;Feng, H.;Fenyuk, A. B.;Martinez, P. F.;Perez, S. F.;Ferrag, S.;Ferrando, J.;Ferrari, A.;Ferrari, P.;Ferrari, R.;de Lima, D. E. F.;Ferrer, A.;Ferrere, D.;Ferretti, C.;Parodi, A. F.;Fiascaris, M.;Fiedler, F.;Filipcic, A.;Filipuzzi, M.;Filthaut, F.;Fincke-Keeler, M.;Finelli, K. D.;Fiolhais, M. C. N.;Fiorini, L.;Firan, A.;Fischer, A.;Fischer, C.;Fischer, J.;Fisher, W. C.;Fitzgerald, E. A.;Flechl, M.;Fleck, I.;Fleischmann, P.;Fleischmann, S.;Fletcher, G. T.;Fletcher, G.;Flick, T.;Floderus, A.;Castillo, L. R. F.;Flowerdew, M. J.;Formica, A.;Forti, A.;Fournier, D.;Fox, H.;Fracchia, S.;Francavilla, P.;Franchini, M.;Francis, D.;Franconi, L.;Franklin, M.;Fraternali, M.;Freeborn, D.;French, S. T.;Friedrich, F.;Froidevaux, D.;Frost, J. A.;Fukunaga, C.;Torregrosa, E. F.;Fulsom, B. G.;Fuster, J.;Gabaldon, C.;Gabizon, O.;Gabrielli, A.;Gabrielli, A.;Gadatsch, S.;Gadomski, S.;Gagliardi, G.;Gagnon, P.;Galea, C.;Galhardo, B.;Gallas, E. J.;Gallop, B. J.;Gallus, P.;Galster, G.;Gan, K. K.;Gao, J.;Gao, Y.;Gao, Y. S.;Walls, F. M. G.;Garberson, F.;Garcia, C.;Navarro, J. E. G.;Garcia-Sciveres, M.;Gardner, R. W.;Garelli, N.;Garonne, V.;Gatti, C.;Gaudiello, A.;Gaudio, G.;Gaur, B.;Gauthier, L.;Gauzzi, P.;Gavrilenko, I. L.;Gay, C.;Gaycken, G.;Gazis, E. N.;Ge, P.;Gecse, Z.;Gee, C. N. P.;Geerts, D. A. A.;Geich-Gimbel, C.;Geisler, M. P.;Gemme, C.;Genest, M. H.;Gentile, S.;George, M.;George, S.;Gerbaudo, D.;Gershon, A.;Ghazlane, H.;Giacobbe, B.;Giagu, S.;Giangiobbe, V.;Giannetti, P.;Gibbard, B.;Gibson, S. M.;Gilchriese, M.;Gillam, T. P. S.;Gillberg, D.;Gilles, G.;Gingrich, D. M.;Giokaris, N.;Giordani, M. P.;Giorgi, F. M.;Giorgi, F. M.;Giraud, P. F.;Giromini, P.;Giugni, D.;Giuliani, C.;Giulini, M.;Gjelsten, B. K.;Gkaitatzis, S.;Gkialas, I.;Gkougkousis, E. L.;Gladilin, L. K.;Glasman, C.;Glatzer, J.;Glaysher, P. C. F.;Glazov, A.;Goblirsch-Kolb, M.;Goddard, J. R.;Godlewski, J.;Goldfarb, S.;Golling, T.;Golubkov, D.;Gomes, A.;Goncalo, R.;Da Costa, Jgpf;Gonella, L.;de la Hoz, S. G.;Parra, G. G.;Gonzalez-Sevilla, S.;Goossens, L.;Gorbounov, P. A.;Gordon, H. A.;Gorelov, I.;Gorini, B.;Gorini, E.;Gorisek, A.;Gornicki, E.;Goshaw, A. T.;Gossling, C.;Gostkin, M. I.;Goujdami, D.;Goussiou, A. G.;Govender, N.;Grabas, H. M. X.;Graber, L.;Grabowska-Bold, I.;Grafstrom, P.;Grahn, K. J.;Gramling, J.;Gramstad, E.;Grancagnolo, S.;Grassi, V.;Gratchev, V.;Gray, H. M.;Graziani, E.;Greenwood, Z. D.;Gregersen, K.;Gregor, I. M.;Grenier, P.;Griffiths, J.;Grillo, A. A.;Grimm, K.;Grinstein, S.;Gris, P.;Grivaz, J. F.;Grohs, J. P.;Grohsjean, A.;Gross, E.;Grosse-Knetter, J.;Grossi, G. C.;Grout, Z. J.;Guan, L.;Guenther, J.;Guescini, F.;Guest, D.;Gueta, O.;Guido, E.;Guillemin, T.;Guindon, S.;Gul, U.;Gumpert, C.;Guo, J.;Gupta, S.;Gutierrez, P.;Ortiz, N. G. G.;Gutschow, C.;Guyot, C.;Gwenlan, C.;Gwilliam, C. B.;Haas, A.;Haber, C.;Hadavand, H. K.;Haddad, N.;Haefner, P.;Hagebock, S.;Hajduk, Z.;Hakobyan, H.;Haleem, M.;Haley, J.;Hall, D.;Halladjian, G.;Hallewell, G. D.;Hamacher, K.;Hamal, P.;Hamano, K.;Hamer, M.;Hamilton, A.;Hamity, G. N.;Hamnett, P. G.;Han, L.;Hanagaki, K.;Hanawa, K.;Hance, M.;Hanke, P.;Hanna, R.;Hansen, J. B.;Hansen, J. D.;Hansen, M. C.;Hansen, P. H.;Hara, K.;Hard, A. S.;Harenberg, T.;Hariri, F.;Harkusha, S.;Harrington, R. D.;Harrison, P. F.;Hartjes, F.;Hasegawa, M.;Hasegawa, S.;Hasegawa, Y.;Hasib, A.;Hassani, S.;Haug, S.;Hauser, R.;Hauswald, L.;Havranek, M.;Hawkes, C. M.;Hawkings, R. J.;Hawkins, A. D.;Hayashi, T.;Hayden, D.;Hays, C. P.;Hays, J. M.;Hayward, H. S.;Haywood, S. J.;Head, S. J.;Heck, T.;Hedberg, V.;Heelan, L.;Heim, S.;Heim, T.;Heinemann, B.;Heinrich, L.;Hejbal, J.;Helary, L.;Hellman, S.;Hellmich, D.;Helsens, C.;Henderson, J.;Henderson, R. C. W.;Heng, Y.;Hengler, C.;Henrichs, A.;Correia, A. M. H.;Henrot-Versille, S.;Herbert, G. H.;Jimenez, Y. H.;Herrberg-Schubert, R.;Herten, G.;Hertenberger, R.;Hervas, L.;Hesketh, G. G.;Hessey, N. P.;Hetherly, W.;Hickling, R.;Higon-Rodriguez, E.;Hill, E.;Hill, J. C.;Hiller, K. H.;Hillier, S. J.;Hinchliffe, I.;Hines, E.;Hinman, R. R.;Hirose, M.;Hirschbuehl, D.;Hobbs, J.;Hod, N.;Hodgkinson, M. C.;Hodgson, P.;Hoecker, A.;Hoeferkamp, M. R.;Hoenig, F.;Hohlfeld, M.;Hohn, D.;Holmes, T. R.;Hong, T. M.;van Huysduynen, L. H.;Hopkins, W. H.;Horii, Y.;Horton, A. J.;Hostachy, J. Y.;Hou, S.;Hoummada, A.;Howard, J.;Howarth, J.;Hrabovsky, M.;Hristova, I.;Hrivnac, J.;Hryn'ova, T.;Hrynevich, A.;Hsu, C.;Hsu, P. J.;Hsu, S. C.;Hu, D.;Hu, Q.;Hu, X.;Huang, Y.;Hubacek, Z.;Hubaut, F.;Huegging, F.;Huffman, T. B.;Hughes, E. W.;Hughes, G.;Huhtinen, M.;Hulsing, T. A.;Huseynov, N.;Huston, J.;Huth, J.;Iacobucci, G.;Iakovidis, G.;Ibragimov, I.;Iconomidou-Fayard, L.;Ideal, E.;Idrissi, Z.;Iengo, P.;Igonkina, O.;Iizawa, T.;Ikegami, Y.;Ikematsu, K.;Ikeno, M.;Ilchenko, Y.;Iliadis, D.;Ilic, N.;Inamaru, Y.;Ince, T.;Ioannou, P.;Iodice, M.;Iordanidou, K.;Ippolito, V.;Quiles, A. I.;Isaksson, C.;Ishino, M.;Ishitsuka, M.;Ishmukhametov, R.;Issever, C.;Istin, S.;Ponce, J. M. I.;Iuppa, R.;Ivarsson, J.;Iwanski, W.;Iwasaki, H.;Izen, J. M.;Izzo, V.;Jabbar, S.;Jackson, B.;Jackson, M.;Jackson, P.;Jaekel, M. R.;Jain, V.;Jakobs, K.;Jakobsen, S.;Jakoubek, T.;Jakubek, J.;Jamin, D. O.;Jana, D. K.;Jansen, E.;Jansky, R. W.;Janssen, J.;Janus, M.;Jarlskog, G.;Javadov, N.;Javurek, T.;Jeanty, L.;Jejelava, J.;Jeng, G. Y.;Jennens, D.;Jenni, P.;Jentzsch, J.;Jeske, C.;Jezequel, S.;Ji, H.;Jia, J.;Jiang, Y.;Jiggins, S.;Pena, J. J.;Jin, S.;Jinaru, A.;Jinnouchi, O.;Joergensen, M. D.;Johansson, P.;Johns, K. A.;Jon-And, K.;Jones, G.;Jones, R. W. L.;Jones, T. J.;Jongmanns, J.;Jorge, P. M.;Joshi, K. D.;Jovicevic, J.;Ju, X.;Jung, C. A.;Jussel, P.;Rozas, A. J.;Kaci, M.;Kaczmarska, A.;Kado, M.;Kagan, H.;Kagan, M.;Kahn, S. J.;Kajomovitz, E.;Kalderon, C. W.;Kama, S.;Kamenshchikov, A.;Kanaya, N.;Kaneda, M.;Kaneti, S.;Kantserov, V. A.;Kanzaki, J.;Kaplan, B.;Kapliy, A.;Kar, D.;Karakostas, K.;Karamaoun, A.;Karastathis, N.;Kareem, M. J.;Karnevskiy, M.;Karpov, S. N.;Karpova, Z. M.;Karthik, K.;Kartvelishvili, V.;Karyukhin, A. N.;Kashif, L.;Kass, R. D.;Kastanas, A.;Kataoka, Y.;Katre, A.;Katzy, J.;Kawagoe, K.;Kawamoto, T.;Kawamura, G.;Kazama, S.;Kazanin, V. F.;Kazarinov, M. Y.;Keeler, R.;Kehoe, R.;Keller, J. S.;Kempster, J. J.;Keoshkerian, H.;Kepka, O.;Kersevan, B. P.;Kersten, S.;Keyes, R. A.;Khalil-zada, F.;Khandanyan, H.;Khanov, A.;Kharlamov, A. G.;Khoo, T. J.;Khovanskiy, V.;Khramov, E.;Khubua, J.;Kim, H. Y.;Kim, H.;Kim, S. H.;Kim, Y.;Kimura, N.;Kind, O. M.;King, B. T.;King, M.;King, R. S. B.;King, S. B.;Kirk, J.;Kiryunin, A. E.;Kishimoto, T.;Kisielewska, D.;Kiss, F.;Kiuchi, K.;Kivernyk, O.;Kladiva, E.;Klein, M. H.;Klein, M.;Klein, U.;Kleinknecht, K.;Klimek, P.;Klimentov, A.;Klingenberg, R.;Klinger, J. A.;Klioutchnikova, T.;Kluge, E. E.;Kluit, P.;Kluth, S.;Kneringer, E.;Knoops, Ebfg;Knue, A.;Kobayashi, A.;Kobayashi, D.;Kobayashi, T.;Kobel, M.;Kocian, M.;Kodys, P.;Koffas, T.;Koffeman, E.;Kogan, L. A.;Kohlmann, S.;Kohout, Z.;Kohriki, T.;Koi, T.;Kolanoski, H.;Koletsou, I.;Komar, A. A.;Komori, Y.;Kondo, T.;Kondrashova, N.;Koneke, K.;Konig, A. C.;Konig, S.;Kono, T.;Konoplich, R.;Konstantinidis, N.;Kopeliansky, R.;Koperny, S.;Kopke, L.;Kopp, A. K.;Korcyl, K.;Kordas, K.;Korn, A.;Korol, A. A.;Korolkov, I.;Korolkova, E. V.;Kortner, O.;Kortner, S.;Kosek, T.;Kostyukhin, V. V.;Kotov, V. M.;Kotwal, A.;Kourkoumeli-Charalampidi, A.;Kourkoumelis, C.;Kouskoura, V.;Koutsman, A.;Kowalewski, R.;Kowalski, T. Z.;Kozanecki, W.;Kozhin, A. S.;Kramarenko, V. A.;Kramberger, G.;Krasnopevtsev, D.;Krasznahorkay, A.;Kraus, J. K.;Kravchenko, A.;Kreiss, S.;Kretz, M.;Kretzschmar, J.;Kreutzfeldt, K.;Krieger, P.;Krizka, K.;Kroeninger, K.;Kroha, H.;Kroll, J.;Kroseberg, J.;Krstic, J.;Kruchonak, U.;Kruger, H.;Krumnack, N.;Krumshteyn, Z. V.;Kruse, A.;Kruse, M. C.;Kruskal, M.;Kubota, T.;Kucuk, H.;Kuday, S.;Kuehn, S.;Kugel, A.;Kuger, F.;Kuhl, A.;Kuhl, T.;Kukhtin, V.;Kulchitsky, Y.;Kuleshov, S.;Kuna, M.;Kunigo, T.;Kupco, A.;Kurashige, H.;Kurochkin, Y. A.;Kurumida, R.;Kus, V.;Kuwertz, E. S.;Kuze, M.;Kvita, J.;Kwan, T.;Kyriazopoulos, D.;La Rosa, A.;Navarro, J. L. L.;La Rotonda, L.;Lacasta, C.;Lacava, F.;Lacey, J.;Lacker, H.;Lacour, D.;Lacuesta, V. R.;Ladygin, E.;Lafaye, R.;Laforge, B.;Lagouri, T.;Lai, S.;Lambourne, L.;Lammers, S.;Lampen, C. L.;Lampl, W.;Lancon, E.;Landgraf, U.;Landon, M. P. J.;Lang, V. S.;Lange, J. C.;Lankford, A. J.;Lanni, F.;Lantzsch, K.;Laplace, S.;Lapoire, C.;Laporte, J. F.;Lari, T.;Manghi, F. L.;Lassnig, M.;Laurelli, P.;Lavrijsen, W.;Law, A. T.;Laycock, P.;Le Dortz, O.;Le Guirriec, E.;Le Menedeu, E.;LeBlanc, M.;LeCompte, T.;Ledroit-Guillon, F.;Lee, C. A.;Lee, S. C.;Lee, L.;Lefebvre, G.;Lefebvre, M.;Legger, F.;Leggett, C.;Lehan, A.;Miotto, G. L.;Lei, X.;Leight, W. A.;Leisos, A.;Leister, A. G.;Leite, M. A. L.;Leitner, R.;Lellouch, D.;Lemmer, B.;Leney, K. J. C.;Lenz, T.;Lenzi, B.;Leone, R.;Leone, S.;Leonidopoulos, C.;Leontsinis, S.;Leroy, C.;Lester, C. G.;Levchenko, M.;Leveque, J.;Levin, D.;Levinson, L. J.;Levy, M.;Lewis, A.;Leyko, A. M.;Leyton, M.;Li, B.;Li, H.;Li, H. L.;Li, L.;Li, L.;Li, S.;Li, Y.;Liang, Z.;Liao, H.;Liberti, B.;Liblong, A.;Lichard, P.;Lie, K.;Liebal, J.;Liebig, W.;Limbach, C.;Limosani, A.;Lin, S. C.;Lin, T. H.;Linde, F.;Lindquist, B. E.;Linnemann, J. T.;Lipeles, E.;Lipniacka, A.;Lisovyi, M.;Liss, T. M.;Lissauer, D.;Lister, A.;Litke, A. M.;Liu, B.;Liu, D.;Liu, J.;Liu, J. B.;Liu, K.;Liu, L.;Liu, M.;Liu, M.;Liu, Y.;Livan, M.;Lleres, A.;Merino, J. L.;Lloyd, S. L.;Lo Sterzo, F.;Lobodzinska, E.;Loch, P.;Lockman, W. S.;Loebinger, F. K.;Loevschall-Jensen, A. E.;Loginov, A.;Lohse, T.;Lohwasser, K.;Lokajicek, M.;Long, B. A.;Long, J. D.;Long, R. E.;Looper, K. A.;Lopes, L.;Mateos, D. L.;Paredes, B. L.;Paz, I. L.;Lorenz, J.;Martinez, N. L.;Losada, M.;Loscutoff, P.;Losel, P. J.;Lou, X.;Lounis, A.;Love, J.;Love, P. A.;Lu, N.;Lubatti, H. J.;Luci, C.;Lucotte, A.;Luehring, F.;Lukas, W.;Luminari, L.;Lundberg, O.;Lund-Jensen, B.;Lynn, D.;Lysak, R.;Lytken, E.;Ma, H.;Ma, L. L.;Maccarrone, G.;Macchiolo, A.;Macdonald, C. M.;Miguens, J. M.;Macina, D.;Madaffari, D.;Madar, R.;Maddocks, H. J.;Mader, W. F.;Madsen, A.;Maeland, S.;Maeno, T.;Maevskiy, A.;Magradze, E.;Mahboubi, K.;Mahlstedt, J.;Maiani, C.;Maidantchik, C.;Maier, A. A.;Maier, T.;Maio, A.;Majewski, S.;Makida, Y.;Makovec, N.;Malaescu, B.;Malecki, P.;Maleev, V. P.;Malek, F.;Mallik, U.;Malon, D.;Malone, C.;Maltezos, S.;Malyshev, V. M.;Malyukov, S.;Mamuzic, J.;Mancini, G.;Mandelli, B.;Mandelli, L.;Mandic, I.;Mandrysch, R.;Maneira, J.;Manfredini, A.;de Andrade, L. M.;Ramos, J. M.;Mann, A.;Manning, P. M.;Manousakis-Katsikakis, A.;Mansoulie, B.;Mantifel, R.;Mantoani, M.;Mapelli, L.;March, L.;Marchiori, G.;Marcisovsky, M.;Marino, C. P.;Marjanovic, M.;Marroquim, F.;Marsden, S. P.;Marshall, Z.;Marti, L. F.;Marti-Garcia, S.;Martin, B.;Martin, T. A.;Martin, V. J.;Latour, B. M. D.;Martinez, M.;Martin-Haugh, S.;Martoiu, V. S.;Martyniuk, A. C.;Marx, M.;Marzano, F.;Marzin, A.;Masetti, L.;Mashimo, T.;Mashinistov, R.;Masik, J.;Maslennikov, A. L.;Massa, I.;Massa, L.;Massol, N.;Mastrandrea, P.;Mastroberardino, A.;Masubuchi, T.;Mattig, P.;Mattmann, J.;Maurer, J.;Maxfield, S. J.;Maximov, D. A.;Mazini, R.;Mazza, S. M.;Mazzaferro, L.;Mc Goldrick, G.;Mc Kee, S. P.;McCarn, A.;McCarthy, R. L.;McCarthy, T. G.;McCubbin, N. A.;McFarlane, K. W.;McFayden, J. A.;McHedlidze, G.;McMahon, S. J.;McPherson, R. A.;Medinnis, M.;Meehan, S.;Mehlhase, S.;Mehta, A.;Meier, K.;Meineck, C.;Meirose, B.;Garcia, B. R. M.;Meloni, F.;Mengarelli, A.;Menke, S.;Meoni, E.;Mercurio, K. M.;Mergelmeyer, S.;Mermod, P.;Merola, L.;Meroni, C.;Merritt, F. S.;Messina, A.;Metcalfe, J.;Mete, A. S.;Meyer, C.;Meyer, C.;Meyer, J. P.;Meyer, J.;Middleton, R. P.;Miglioranzi, S.;Mijovic, L.;Mikenberg, G.;Mikestikova, M.;Mikuz, M.;Milesi, M.;Milic, A.;Miller, D. W.;Mills, C.;Milov, A.;Milstead, D. A.;Minaenko, A. A.;Minami, Y.;Minashvili, I. A.;Mincer, A. I.;Mindur, B.;Mineev, M.;Ming, Y.;Mir, L. M.;Mitani, T.;Mitrevski, J.;Mitsou, V. A.;Miucci, A.;Miyagawa, P. S.;Mjornmark, J. U.;Moa, T.;Mochizuki, K.;Mohapatra, S.;Mohr, W.;Molander, S.;Moles-Valls, R.;Monig, K.;Monini, C.;Monk, J.;Monnier, E.;Berlingen, J. M.;Monticelli, F.;Monzani, S.;Moore, R. W.;Morange, N.;Moreno, D.;Llacer, M. M.;Morettini, P.;Morgenstern, M.;Morii, M.;Morinaga, M.;Morisbak, V.;Moritz, S.;Morley, A. K.;Mornacchi, G.;Morris, J. D.;Mortensen, S. S.;Morton, A.;Morvaj, L.;Mosidze, M.;Moss, J.;Motohashi, K.;Mount, R.;Mountricha, E.;Mouraviev, S. V.;Moyse, E. J. W.;Muanza, S.;Mudd, R. D.;Mueller, F.;Mueller, J.;Mueller, K.;Mueller, R. S. P.;Mueller, T.;Muenstermann, D.;Mullen, P.;Munwes, Y.;Quijada, J. A. M.;Murray, W. J.;Musheghyan, H.;Musto, E.;Myagkov, A. G.;Myska, M.;Nackenhorst, O.;Nadal, J.;Nagai, K.;Nagai, R.;Nagai, Y.;Nagano, K.;Nagarkar, A.;Nagasaka, Y.;Nagata, K.;Nagel, M.;Nagy, E.;Nairz, A. M.;Nakahama, Y.;Nakamura, K.;Nakamura, T.;Nakano, I.;Namasivayam, H.;Garcia, R. F. N.;Narayan, R.;Naumann, T.;Navarro, G.;Nayyar, R.;Neal, H. A.;Nechaeva, P. Y.;Neep, T. J.;Nef, P. D.;Negri, A.;Negrini, M.;Nektarijevic, S.;Nellist, C.;Nelson, A.;Nemecek, S.;Nemethy, P.;Nepomuceno, A. A.;Nessi, M.;Neubauer, M. S.;Neumann, M.;Neves, R. M.;Nevski, P.;Newman, P. R.;Nguyen, D. H.;Nickerson, R. B.;Nicolaidou, R.;Nicquevert, B.;Nielsen, J.;Nikiforou, N.;Nikiforov, A.;Nikolaenko, V.;Nikolic-Audit, I.;Nikolopoulos, K.;Nilsen, J. K.;Nilsson, P.;Ninomiya, Y.;Nisati, A.;Nisius, R.;Nobe, T.;Nomachi, M.;Nomidis, I.;Nooney, T.;Norberg, S.;Nordberg, M.;Novgorodova, O.;Nowak, S.;Nozaki, M.;Nozka, L.;Ntekas, K.;Hanninger, G. N.;Nunnemann, T.;Nurse, E.;Nuti, F.;O'Brien, B. J.;O'Grady, F.;O'Neil, D. C.;O'Shea, V.;Oakham, F. G.;Oberlack, H.;Obermann, T.;Ocariz, J.;Ochi, A.;Ochoa, I.;Ochoa-Ricoux, J. P.;Oda, S.;Odaka, S.;Ogren, H.;Oh, A.;Oh, S. H.;Ohm, C. C.;Ohman, H.;Oide, H.;Okamura, W.;Okawa, H.;Okumura, Y.;Okuyama, T.;Olariu, A.;Pino, S. A. O.;Damazio, D. O.;Garcia, E. O.;Olszewski, A.;Olszowska, J.;Onofre, A.;Onyisi, P. U. E.;Oram, C. J.;Oreglia, M. J.;Oren, Y.;Orestano, D.;Orlando, N.;Barrera, C. O.;Orr, R. S.;Osculati, B.;Ospanov, R.;Garzon, G. O. Y.;Otono, H.;Ouchrif, M.;Ouellette, E. A.;Ould-Saada, F.;Ouraou, A.;Oussoren, K. P.;Ouyang, Q.;Ovcharova, A.;Owen, M.;Owen, R. E.;Ozcan, V. E.;Ozturk, N.;Pachal, K.;Pages, A. P.;Aranda, C. P.;Pagacova, M.;Griso, S. P.;Paganis, E.;Pahl, C.;Paige, F.;Pais, P.;Pajchel, K.;Palacino, G.;Palestini, S.;Palka, M.;Pallin, D.;Palma, A.;Pan, Y. B.;Panagiotopoulou, E.;Pandini, C. E.;Vazquez, J. G. P.;Pani, P.;Panitkin, S.;Pantea, D.;Paolozzi, L.;Papadopoulou, T. D.;Papageorgiou, K.;Paramonov, A.;Hernandez, D. P.;Parker, M. A.;Parker, K. A.;Parodi, F.;Parsons, J. A.;Parzefall, U.;Pasqualucci, E.;Passaggio, S.;Pastore, F.;Pastore, F.;Pasztor, G.;Pataraia, S.;Patel, N. D.;Pater, J. R.;Pauly, T.;Pearce, J.;Pearson, B.;Pedersen, L. E.;Pedersen, M.;Lopez, S. P.;Pedro, R.;Peleganchuk, S. V.;Pelikan, D.;Peng, H.;Penning, B.;Penwell, J.;Perepelitsa, D. V.;Codina, E. P.;Garcia-Estan, M. T. P.;Perini, L.;Pernegger, H.;Perrella, S.;Peschke, R.;Peshekhonov, V. D.;Peters, K.;Peters, R. F. Y.;Petersen, B. A.;Petersen, T. C.;Petit, E.;Petridis, A.;Petridou, C.;Petrolo, E.;Petrucci, F.;Pettersson, N. E.;Pezoa, R.;Phillips, P. W.;Piacquadio, G.;Pianori, E.;Picazio, A.;Piccaro, E.;Piccinini, M.;Pickering, M. A.;Piegaia, R.;Pignotti, D. T.;Pilcher, J. E.;Pilkington, A. D.;Pina, J.;Pinamonti, M.;Pinfold, J. L.;Pingel, A.;Pinto, B.;Pires, S.;Pitt, M.;Pizio, C.;Plazak, L.;Pleier, M. A.;Pleskot, V.;Plotnikova, E.;Plucinski, P.;Pluth, D.;Poettgen, R.;Poggioli, L.;Pohl, D.;Polesello, G.;Policicchio, A.;Polifka, R.;Polini, A.;Pollard, C. S.;Polychronakos, V.;Pommes, K.;Pontecorvo, L.;Pope, B. G.;Popeneciu, G. A.;Popovic, D. S.;Poppleton, A.;Pospisil, S.;Potamianos, K.;Potrap, I. N.;Potter, C. J.;Potter, C. T.;Poulard, G.;Poveda, J.;Pozdnyakov, V.;Pralavorio, P.;Pranko, A.;Prasad, S.;Prell, S.;Price, D.;Price, L. E.;Primavera, M.;Prince, S.;Proissl, M.;Prokofiev, K.;Prokoshin, F.;Protopapadaki, E.;Protopopescu, S.;Proudfoot, J.;Przybycien, M.;Ptacek, E.;Puddu, D.;Pueschel, E.;Puldon, D.;Purohit, M.;Puzo, P.;Qian, J.;Qin, G.;Qin, Y.;Quadt, A.;Quarrie, D. R.;Quayle, W. B.;Queitsch-Maitland, M.;Quilty, D.;Raddum, S.;Radeka, V.;Radescu, V.;Radhakrishnan, S. K.;Radloff, P.;Rados, P.;Ragusa, F.;Rahal, G.;Rajagopalan, S.;Rammensee, M.;Rangel-Smith, C.;Rauscher, F.;Rave, S.;Ravenscroft, T.;Raymond, M.;Read, A. L.;Readioff, N. P.;Rebuzzi, D. M.;Redelbach, A.;Redlinger, G.;Reece, R.;Reeves, K.;Rehnisch, L.;Reisin, H.;Relich, M.;Rembser, C.;Ren, H.;Renaud, A.;Rescigno, M.;Resconi, S.;Rezanova, O. L.;Reznicek, P.;Rezvani, R.;Richter, R.;Richter, S.;Richter-Was, E.;Ricken, O.;Ridel, M.;Rieck, P.;Riegel, C. J.;Rieger, J.;Rijssenbeek, M.;Rimoldi, A.;Rinaldi, L.;Ristic, B.;Ritsch, E.;Riu, I.;Rizatdinova, F.;Rizvi, E.;Robertson, S. H.;Robichaud-Veronneau, A.;Robinson, D.;Robinson, J. E. M.;Robson, A.;Roda, C.;Roe, S.;Rohne, O.;Rolli, S.;Romaniouk, A.;Romano, M.;Saez, S. M. R.;Adam, E. R.;Rompotis, N.;Ronzani, M.;Roos, L.;Ros, E.;Rosati, S.;Rosbach, K.;Rose, P.;Rosendahl, P. L.;Rosenthal, O.;Rossetti, V.;Rossi, E.;Rossi, L. P.;Rosten, R.;Rotaru, M.;Roth, I.;Rothberg, J.;Rousseau, D.;Royon, C. R.;Rozanov, A.;Rozen, Y.;Ruan, X.;Rubbo, F.;Rubinskiy, I.;Rud, V. I.;Rudolph, C.;Rudolph, M. S.;Ruhr, F.;Ruiz-Martinez, A.;Rurikova, Z.;Rusakovich, N. A.;Ruschke, A.;Russell, H. L.;Rutherfoord, J. P.;Ruthmann, N.;Ryabov, Y. F.;Rybar, M.;Rybkin, G.;Ryder, N. C.;Saavedra, A. F.;Sabato, G.;Sacerdoti, S.;Saddique, A.;Sadrozinski, H. F. W.;Sadykov, R.;Tehrani, F. S.;Saimpert, M.;Sakamoto, H.;Sakurai, Y.;Salamanna, G.;Salamon, A.;Saleem, M.;Salek, D.;De Bruin, P. H. S.;Salihagic, D.;Salnikov, A.;Salt, J.;Salvatore, D.;Salvatore, F.;Salvucci, A.;Salzburger, A.;Sampsonidis, D.;Sanchez, A.;Sanchez, J.;Martinez, V. S.;Sandaker, H.;Sandbach, R. L.;Sander, H. G.;Sanders, M. P.;Sandhoff, M.;Sandoval, C.;Sandstroem, R.;Sankey, D. P. C.;Sannino, M.;Sansoni, A.;Santoni, C.;Santonico, R.;Santos, H.;Castillo, I. S.;Sapp, K.;Sapronov, A.;Saraiva, J. G.;Sarrazin, B.;Sasaki, O.;Sasaki, Y.;Sato, K.;Sauvage, G.;Sauvan, E.;Savage, G.;Savard, P.;Sawyer, C.;Sawyer, L.;Saxon, J.;Sbarra, C.;Sbrizzi, A.;Scanlon, T.;Scannicchio, D. A.;Scarcella, M.;Scarfone, V.;Schaarschmidt, J.;Schacht, P.;Schaefer, D.;Schaefer, R.;Schaeffer, J.;Schaepe, S.;Schaetzel, S.;Schafer, U.;Schaffer, A. C.;Schaile, D.;Schamberger, R. D.;Scharf, V.;Schegelsky, V. A.;Scheirich, D.;Schernau, M.;Schiavi, C.;Schillo, C.;Schioppa, M.;Schlenker, S.;Schmidt, E.;Schmieden, K.;Schmitt, C.;Schmitt, S.;Schmitt, S.;Schneider, B.;Schnellbach, Y. J.;Schnoor, U.;Schoeffel, L.;Schoening, A.;Schoenrock, B. D.;Schopf, E.;Schorlemmer, A. L. S.;Schott, M.;Schouten, D.;Schovancova, J.;Schramm, S.;Schreyer, M.;Schroeder, C.;Schuh, N.;Schultens, M. J.;Schultz-Coulon, H. C.;Schulz, H.;Schumacher, M.;Schumm, B. A.;Schune, P.;Schwanenberger, C.;Schwartzman, A.;Schwarz, T. A.;Schwegler, P.;Schwemling, P.;Schwienhorst, R.;Schwindling, J.;Schwindt, T.;Schwoerer, M.;Sciacca, F. G.;Scifo, E.;Sciolla, G.;Scuri, F.;Scutti, F.;Searcy, J.;Sedov, G.;Sedykh, E.;Seema, P.;Seidel, S. C.;Seiden, A.;Seifert, F.;Seixas, J. M.;Sekhniaidze, G.;Sekhon, K.;Sekula, S. J.;Selbach, K. E.;Seliverstov, D. M.;Semprini-Cesari, N.;Serfon, C.;Serin, L.;Serkin, L.;Serre, T.;Sessa, M.;Seuster, R.;Severini, H.;Sfiligoj, T.;Sforza, F.;Sfyrla, A.;Shabalina, E.;Shamim, M.;Shan, L. Y.;Shang, R.;Shank, J. T.;Shapiro, M.;Shatalov, P. B.;Shaw, K.;Shaw, S. M.;Shcherbakova, A.;Shehu, C. Y.;Sherwood, P.;Shi, L.;Shimizu, S.;Shimmin, C. O.;Shimojima, M.;Shiyakova, M.;Shmeleva, A.;Saadi, D. S.;Shochet, M. J.;Shojaii, S.;Shrestha, S.;Shulga, E.;Shupe, M. A.;Shushkevich, S.;Sicho, P.;Sidiropoulou, O.;Sidorov, D.;Sidoti, A.;Siegert, F.;Sijacki, D.;Silva, J.;Silver, Y.;Silverstein, S. B.;Simak, V.;Simard, O.;Simic, L.;Simion, S.;Simioni, E.;Simmons, B.;Simon, D.;Simoniello, R.;Sinervo, P.;Sinev, N. B.;Siragusa, G.;Sisakyan, A. N.;Sivoklokov, S. Y.;Sjolin, J.;Sjursen, T. B.;Skinner, M. B.;Skottowe, H. P.;Skubic, P.;Slater, M.;Slavicek, T.;Slawinska, M.;Sliwa, K.;Smakhtin, V.;Smart, B. H.;Smestad, L.;Smirnov, S. Y.;Smirnov, Y.;Smirnova, L. N.;Smirnova, O.;Smith, M. N. K.;Smith, R. W.;Smizanska, M.;Smolek, K.;Snesarev, A. A.;Snidero, G.;Snyder, S.;Sobie, R.;Socher, F.;Soffer, A.;Soh, D. A.;Solans, C. A.;Solar, M.;Solc, J.;Soldatov, E. Y.;Soldevila, U.;Solodkov, A. A.;Soloshenko, A.;Solovyanov, O. V.;Solovyev, V.;Sommer, P.;Song, H. Y.;Soni, N.;Sood, A.;Sopczak, A.;Sopko, B.;Sopko, V.;Sorin, V.;Sosa, D.;Sosebee, M.;Sotiropoulou, C. L.;Soualah, R.;Soueid, P.;Soukharev, A. M.;South, D.;Sowden, B. C.;Spagnolo, S.;Spalla, M.;Spano, F.;Spearman, W. R.;Spettel, F.;Spighi, R.;Spigo, G.;Spiller, L. A.;Spousta, M.;Spreitzer, T.;St Denis, R. D.;Staerz, S.;Stahlman, J.;Stamen, R.;Stamm, S.;Stanecka, E.;Stanescu, C.;Stanescu-Bellu, M.;Stanitzki, M. M.;Stapnes, S.;Starchenko, E. A.;Stark, J.;Staroba, P.;Starovoitov, P.;Staszewski, R.;Stavina, P.;Steinberg, P.;Stelzer, B.;Stelzer, H. J.;Stelzer-Chilton, O.;Stenzel, H.;Stern, S.;Stewart, G. A.;Stillings, J. A.;Stockton, M. C.;Stoebe, M.;Stoicea, G.;Stolte, P.;Stonjek, S.;Stradling, A. R.;Straessner, A.;Stramaglia, M. E.;Strandberg, J.;Strandberg, S.;Strandlie, A.;Strauss, E.;Strauss, M.;Strizenec, P.;Strohmer, R.;Strom, D. M.;Stroynowski, R.;Strubig, A.;Stucci, S. A.;Stugu, B.;Styles, N. A.;Su, D.;Su, J.;Subramaniam, R.;Succurro, A.;Sugaya, Y.;Suhr, C.;Suk, M.;Sulin, V. V.;Sultansoy, S.;Sumida, T.;Sun, S.;Sun, X.;Sundermann, J. E.;Suruliz, K.;Susinno, G.;Sutton, M. R.;Suzuki, S.;Suzuki, Y.;Svatos, M.;Swedish, S.;Swiatlowski, M.;Sykora, I.;Sykora, T.;Ta, D.;Taccini, C.;Tackmann, K.;Taenzer, J.;Taffard, A.;Tafirout, R.;Taiblum, N.;Takai, H.;Takashima, R.;Takeda, H.;Takeshita, T.;Takubo, Y.;Talby, M.;Talyshev, A. A.;Tam, J. Y. C.;Tan, K. G.;Tanaka, J.;Tanaka, R.;Tanaka, S.;Tannenwald, B. B.;Tannoury, N.;Tapprogge, S.;Tarem, S.;Tarrade, F.;Tartarelli, G. F.;Tas, P.;Tasevsky, M.;Tashiro, T.;Tassi, E.;Delgado, A. T.;Tayalati, Y.;Taylor, F. E.;Taylor, G. N.;Taylor, W.;Teischinger, F. A.;Castanheira, M. T. D.;Teixeira-Dias, P.;Temming, K. K.;Ten Kate, H.;Teng, P. K.;Teoh, J. J.;Tepel, F.;Terada, S.;Terashi, K.;Terron, J.;Terzo, S.;Testa, M.;Teuscher, R. J.;Therhaag, J.;Theveneaux-Pelzer, T.;Thomas, J. P.;Thomas-Wilsker, J.;Thompson, E. N.;Thompson, P. D.;Thompson, R. J.;Thompson, A. S.;Thomsen, L. A.;Thomson, E.;Thomson, M.;Thun, R. P.;Tibbetts, M. J.;Torres, R. E. T.;Tikhomirov, V. O.;Tikhonov, Y. A.;Timoshenko, S.;Tiouchichine, E.;Tipton, P.;Tisserant, S.;Todorov, T.;Todorova-Nova, S.;Tojo, J.;Tokar, S.;Tokushuku, K.;Tollefson, K.;Tolley, E.;Tomlinson, L.;Tomoto, M.;Tompkins, L.;Toms, K.;Torrence, E.;Torres, H.;Pastor, E. T.;Toth, J.;Touchard, F.;Tovey, D. R.;Trefzger, T.;Tremblet, L.;Tricoli, A.;Trigger, I. M.;Trincaz-Duvoid, S.;Tripiana, M. F.;Trischuk, W.;Trocme, B.;Troncon, C.;Trottier-McDonald, M.;Trovatelli, M.;True, P.;Truong, L.;Trzebinski, M.;Trzupek, A.;Tsarouchas, C.;Tseng, J. C. L.;Tsiareshka, P. V.;Tsionou, D.;Tsipolitis, G.;Tsirintanis, N.;Tsiskaridze, S.;Tsiskaridze, V.;Tskhadadze, E. G.;Tsukerman, II;Tsulaia, V.;Tsuno, S.;Tsybychev, D.;Tudorache, A.;Tudorache, V.;Tuna, A. N.;Tupputi